2020
DOI: 10.1016/j.ejphar.2020.173419
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid-induced apoptosis and cell cycle arrest in triple-negative breast cancer cells

Abstract: Rosmarinic acid (RA) is a polyphenolic compound with various pharmacological properties, including, anti-inflammatory, immunomodulatory, and neuroprotective, as well as having antioxidant and anticancer activities. This study evaluated the effects and mechanisms of RA in two racially different triple-negative breast cancer (TNBC) cell lines. Results obtained show that RA significantly caused cytotoxic and antiproliferative effects in both cell lines in a dose- and time-dependent manner. Remarkably, RA induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 65 publications
0
60
0
1
Order By: Relevance
“…These results indicate that RA-SFNs can be regarded as a potential drug targeting cervical and breast cancer. Previous studies have also found that RA induced apoptosis in several cancer cell lines [ 10 , 46 ].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…These results indicate that RA-SFNs can be regarded as a potential drug targeting cervical and breast cancer. Previous studies have also found that RA induced apoptosis in several cancer cell lines [ 10 , 46 ].…”
Section: Resultsmentioning
confidence: 85%
“…Several in vitro studies with RA found in the literature have shown the ability of RA to inhibit cell proliferation and induce cell cycle arrest in various cancer cells [ 10 , 11 ]. The apoptosis phase after treatment with RA-SFNs was highly evaluated in the following experiment for both cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier study has shown that limonene induces apoptosis by inhibiting PI3K/Akt pathway [ 24 ]. Moreover, rosmarinic acid was detected in high concentration in different extracts of H. orientalis L. It was reported that rosmarinic acid has the ability to promote cell arrest in the G₀/G₁ phase and modulate the expression of many apoptosis-involved genes [ 25 ]. Additionally, trans-ferulic acid was found at various percentages in four different extracts of H. orientalis L. This compound has shown antiproliferative activity as well as induced the expression of pro-apoptotic factor Bax, and reduced the expression of pro-survival factor survivin [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al [ 60 ] reported that RA inhibited the proliferation and negatively affected the migratory potential of human oral cancer cells (cell line SCC-15) with a dose-dependent effect. Messeha et al [ 61 ] reported that RA caused significant cytotoxic and antiproliferative effects in two racially different triple-negative breast cancer (TNBC) cell lines in a dose- and time-dependent manner.…”
Section: Biochemical and Health Properties Of The Examined Phenolic Acidsmentioning
confidence: 99%